Design of a Mathematics Teaching Module for Elementary School Based on Ethnomathematics of Buton Traditional Houses to Improve Numerical Literacy Skills - Ekadayanti, Waode; Ili, La; Kadir; Yanti, Noer Rakhmat; Hesti (Jurnal Amal Pendidikan, 2024)
This study aims to design an ethnomathematics-based mathematics teaching module for elementary school, focused on the Traditional House of Buton, to improve numerical literacy skills and assess the feasibility and student responses to the module. The research method used is Research and Development (R&D), following these stages: problem identification, design, validation, implementation, and evaluation. The results show the successful design of the module, which is valid with an average construct validation score of 0,775 and content validation score of 0,772, both categorized as "valid." Student response analysis, involving 15 fourth-grade students, showed a positive response with 84,21%. Before using the module, the average pretest score was 59 (incomplete), and after the module implementation, the average posttest score increased to 88,33 (complete), indicating significant improvement in students' numerical literacy skills. Based on these findings, it can be concluded that the module is valid, practical, and effective in enhancing students' numerical literacy skills.